Examining Gender Disparity Among Superiors in Evaluating their Subordinates in the Manufacturing and the Service Sector - Sujatha, S.; Saleendran, P. T. (Prabandhan: Indian Journal of Management, 2012)
India, like most developing countries, is witnessing a change in the gender-mix of employees in the organized sector. The changing political, economic and psycho-social scenes have given some slow, but steady, impetus to women’s literacy and awareness within the female population. As a result, there is a shift in the labour market in terms of the gender-mix; the number of women job applicants are growing steadily, particularly in the middle rung of the organizations. There is a need to address the problem that arises due to the clash of women’s perceptions, attitudes and behavior that female socialization encourages, with male corporate culture and male rules of career development; with the policies and practices of male-led corporations. Due to career interruptions and turnover, women are less likely to reach top executive positions. Considering this background, the study attempts to know the supervisors’ perception about their male and female subordinates while managing them on the work spot. The research objectives are to know the perceptional difference that exists among the superiors’ while assessing their male and female subordinates in the organization, to know the prevalence of gender disparity in the manufacturing and service sector, and to suggest certain remedies to overcome the flaws.